HUBUNGAN INDEKS MASSA TUBUH (IMT) DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI - Berlian Kusuma Dewi; Suci Nurjanah; Niken Wulan Hasthi Murti (Yakpermas Press, 2023)
Background: Anemia is a condition where there is a lack of red blood cells in the body and is a major problem in developing countries. Nutritional status is suspected to be one of the factors that causes anemia, especially in adolescents. Objective: This study aims to determine the relationship between Body Mass Index (BMI) and the incidence of anemia in female students at Teladan Kertasemaya Vocational School, Indramayu Regency. Research method: Observational analytic with a cross-sectional approach. The population in this research were female students at Teladan Kertasemaya Vocational School, taking into account the inclusion and exclusion criteria with a total research sample of 87 respondents. The instrument used was a questionnaire containing age, menstrual patterns and body mass index (BMI). The analysis used is the Chi-Square correlation test. Results: Most of the respondents were 16 years old (51.7%) with a minimum age of 15 years and a maximum age of 17 years, the BMI of Teladan Vocational High School students. As many as 54% of the Teladan Vocational School students of Kertasemaya had a normal BMI, while 37.9% of the female students were in the lower category. BMI or thin. Most of the female students did not experience anemia (78.2%). Meanwhile, 21.8% of female students showed hemoglobin levels below 12 g/dl. The results of the correlation test with chi-square between BMI and the incidence of anemia showed p = 0.037 (p < 0.05). Conclusion: This study shows that there is a relationship between BMI and the incidence of anemia in female students at Teladan Kertasemaya Vocational School.